Strategi Komunikasi Politik Sarmuji dalam Menambah Kursi Partai Golkar di Daerah Pemilihan Jawa Timur VI pada Pemilu 2024 - Nurfebriansyah, Ahmad Rifki; Djuyandi, Yusa (Jurnal Pemerintahan dan Politik, 2024)
This research explains Sarmuji's political communication strategy in the 2024 elections. Sarmuji is an incumbent who has held a seat in the DPR RI since 2014 and was re-elected in the 2024 elections. Rationally, the opportunity to add seats in the East Java VI electoral district is quite difficult considering the dominance of the PDI-P. On the other hand, throughout the history of the 2004 to 2019 elections, the Golkar Party was only able to bag 1 seat. The aim of this research is to describe and analyze the political communication strategy used by Sarmuji so that he was able to obtain 2 seats. The theory used in this research is Anwar Arifin's Political Communication Strategy. With a conceptual basis on three aspects, namely caring for figures and strengthening institutions, creating togetherness, and building consensus. This research method uses a qualitative methodology based on case studies. The data used is through in-depth interviews and relevant sources. The results of the study show that Sarmuji applies his political communication strategy by showing the strength of his political party institutions, Sarmuji's strength, and using persuasive methods in conveying political messages. Sarmuji shows that he is a figure who is able to understand the audience with his calm and non-explosive attitude. Sarmuji also showed his courage in the political compromise to include Heru Tjahjono in his electoral district and it was proven that his decision led to the Golkar Party gaining 2 seats in the VI East Java electoral district.